Survivorship, Clinical Outcomes, and Radiographic Complications in the Infinity Total Ankle Arthroplasty at Mid-term (Minimum 5-Year) Follow-up - Isabel Shaffrey; Lavan Rajan BA; Emmett M. Omalley; Scott J. Ellis MD; Jonathan Deland MD; Martin O’Malley MD; Jensen K. Henry MD; Constantine Demetracopoulos MD (Foot & Ankle Orthopaedics, 2023)
Category: Ankle Arthritis; Ankle Introduction/Purpose: As the frequency of total ankle arthroplasties (TAA) performed annually has increased significantly over the past decade, several novel TAA implants have entered the market. The Infinity TAA (Stryker, Mahwah, NJ) is a low-profile fixed- bearing implant that was approved for use in the United States in 2014. Although the short-term survivorship and complication rates of the Infinity TAA have been well documented in the literature, mid- to long-term outcome studies of this implant are limited. The aim of this study was to describe the survivorship, reoperation rate, and radiographic and clinical outcomes of the Infinity implant at minimum 5-year follow-up. We hypothesized that there would be no significant drop-off in clinical outcome or alignment from 2-year to 5-year follow-up. Methods: This is a single-institution retrospective review of patients who underwent primary TAA with the Infinity implant from July 2014 to April 2017. Four fellowship-trained foot and ankle surgeons contributed patients. Out of 74 identified ankles, 65 ankles in 64 patients had minimum clinical follow-up of 5 years (mean, 6.5; range, 5.0-8.0) and were included for analysis. Medical records were reviewed to record demographics, surgical data, complications, reoperations, and revisions. Radiographs were assessed to measure preoperative and postoperative alignment, and the incidence of postoperative peri-implant lucencies and cysts. Preoperative, 2-year, and 5-year postoperative Foot and Ankle Outcome Score (FAOS) subscores in the categories of Pain, Symptoms, Activities of Daily Living, Sports, and Quality of Life were obtained. The primary outcome was 5-year survivorship. Secondary outcomes were reoperations with retention of tibial and talar components, radiographic alignment, peri-implant lucencies/cysts, and clinical outcomes (FAOS) scores. Results: Implant survivorship at 5 years was 93.8%, with 4/65 revisions. Three revisions occurred less than 2 years from the index surgery (2/3 for tibial subsidence; 1/3 for tibial and talar subsidence). The fourth revision occurred at 7.1 years due to cystic changes with tibial and talar subsidence. There were 11 reoperations in 10 ankles. Alignment correction achieved surgically (preop coronal deformity 9.0 ± 6.8°; 1Y postop 1.6 ± 1.5°) was maintained at final radiographic follow-up (1.8 ± 1.7°; P = 0.32). There were 16 ankles (24.6%) with peri-implant radiographic abnormalities: 14 cases of lucency (14 tibia, 0 talus) and 3 cases of cysts. FAOS outcomes demonstrated significant improvement from preop to postop in all five domains at 2 years, which were maintained at 5 years. Conclusion: The mid-term outcomes of the Infinity implant in this single-institution study demonstrated good survivorship of 93.8% and improved clinical outcomes at mean 6.3-year follow-up. This was a mid-term follow-up to the 2-year outcome study published at this institution. Radiographic assessment at final follow-up demonstrated that alignment correction was maintained, and there was a 21.5% incidence of asymptomatic periprosthetic lucencies. These results demonstrate that there was no significant change in radiographic or clinical outcomes with this implant after 5 years, which is valuable for surgeons in terms of counseling and following patients in the immediate and mid-term postoperative period.